Federal Republic of Yugoslavia : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
This first national assessment of public procurement in Yugoslavia examines all areas of public procurement operations, including the legislative framework, the performance of regulatory functions, the enforcement regime, the capacity of public sector institutions to conduct procurement and the effects of corruption on procurement. The assessment, which was conducted jointly by the World Bank and the European Bank for Reconstruction and Development (EBRD), was carried out in consultation with counterparts from Federal Ministry of Finance, Federal Ministry of Foreign Economic Relations, the Ministry of Finance and Economy of the Republic of Serbia, and the Ministry of Finance of the Republic of Montenegro. The report sums up key findings, including risk assessment, the strengths and weaknesses of the public procurement system currently in place, and the main features of a proposed action plan.